2017
DOI: 10.1210/en.2017-00254
|View full text |Cite
|
Sign up to set email alerts
|

Deciphering the Function of the Blunt Circadian Rhythm of Melatonin in the Newborn Lamb: Impact on Adrenal and Heart

Abstract: Neonatal lambs, as with human and other neonates, have low arrhythmic endogenous levels of melatonin for several weeks until they start their own pineal rhythm of melatonin production at approximately 2 weeks of life. During pregnancy, daily rhythmic transfer of maternal melatonin to the fetus has important physiological roles in sheep, nonhuman primates, and rats. This melatonin rhythm provides a circadian signal and also participates in adjusting the physiology of several organs in preparation for extrauteri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 62 publications
0
18
0
Order By: Relevance
“…The adrenal gland expresses melatonin receptor (Torres-Farfan et al 2003, Mendez et al 2012, Leliavski et al 2015. A high-amplitude melatonin rhythm imposed on newborn lambs resulted in suppression of the adrenal clock genes PER1, PER2, CRY2, and CLOCK (Seron-Ferre et al 2017), whereas BMAL1 maintained normal clock time-related changes, but with higher values (Torres-Farfan et al 2011, Seron-Ferre et al 2017. Interestingly, the previously described induction of PER1 by ACTH stimulation of the human adrenal gland can be inhibited, in vitro, by simultaneous treatment with melatonin.…”
Section: Melatoninmentioning
confidence: 94%
“…The adrenal gland expresses melatonin receptor (Torres-Farfan et al 2003, Mendez et al 2012, Leliavski et al 2015. A high-amplitude melatonin rhythm imposed on newborn lambs resulted in suppression of the adrenal clock genes PER1, PER2, CRY2, and CLOCK (Seron-Ferre et al 2017), whereas BMAL1 maintained normal clock time-related changes, but with higher values (Torres-Farfan et al 2011, Seron-Ferre et al 2017. Interestingly, the previously described induction of PER1 by ACTH stimulation of the human adrenal gland can be inhibited, in vitro, by simultaneous treatment with melatonin.…”
Section: Melatoninmentioning
confidence: 94%
“…A recent study in newborn lambs showed that during the early postnatal period when endogenous melatonin levels are low, high‐dose exogenous melatonin treatment interfered with the postnatal adaptation of adrenocortical function and heart development (Seron‐Ferre et al . ). Melatonin injections (0.25 mg/kg) on postnatal days 1–5 altered clock‐time related changes in levels of hormones and metabolic markers, affected the expression of clock genes and functional genes in adrenals and heart, and decreased heart/body weight ratio (Seron‐Ferre et al .…”
Section: The Global Burden Of Hypoxic–ischaemic Brain Injurymentioning
confidence: 97%
“…Melatonin injections (0.25 mg/kg) on postnatal days 1–5 altered clock‐time related changes in levels of hormones and metabolic markers, affected the expression of clock genes and functional genes in adrenals and heart, and decreased heart/body weight ratio (Seron‐Ferre et al . ). Although the long‐term consequences of these changes are not known, these data suggest the need for more preclinical and clinical research on the systemic effects of melatonin treatment during the early postnatal period.…”
Section: The Global Burden Of Hypoxic–ischaemic Brain Injurymentioning
confidence: 97%
“…RNA reverse transcription was performed from approximately 2 μg of RNA with 100 ng of random primers and 200 U M-MLV RT (200 U/μl) in a final volume of 20 μl. Gene expression was measured by quantitative reverse transcription polymerase chain reaction (PCR) as previously reported (8). Primers reported in the literature were used to measure egr1, ctgf (15), per1, bmal1, cry1 , glucocorticoid receptor ( nr3c1 ), gapdh , and rplp0 (8).…”
Section: Methodsmentioning
confidence: 99%
“…Previously, we investigated the effects of melatonin in normal term newborn lambs by imposing a high-amplitude melatonin rhythm for 5 days (8). We found that this treatment resulted in a decreased heart weight, changes in cortisol and other plasma variables, changes of gene expression of clock genes and selected functional genes in the adrenal gland and heart.…”
Section: Introductionmentioning
confidence: 99%